PROGRESSIVE METAMORPHISM OF CALC-SILICATE ROCKS FROM THE PRINCE OLAV AND SOYA COASTS, EAST ANTARCTICA - ヒロイ, ヨシクニ; シライシ, カズユキ; モトヨシ, ヨウイチ; カツシマ, タカヨシ; HIROI, Yoshikuni; SHIRAISHI, Kazuyuki; MOTOYOSHI, Yoichi; KATSUSHIMA, Takayoshi (National Institute of Polar Research, 1987)
P(論文) Metamorphosed calc-silicate rocks occur sporadically as small masses enclosed in other high-grade metasedimentary rocks of the Late Proterozoic Lutzow-Holm Complex in the Prince Olav and Soya Coasts, East Antarctica. Southwestward progressive metamorphism of the calc-silicate rocks is clarified which is in good agreement with the results of previous studies on the pelitic and basic-intermediate rocks. Two isograds are mapped on the basis of the continuous reaction epidote+quartz±calcite=grandite garnet+plagioclase+Fe-oxides±scapolite+H_2O and the discontinuous reaction grossular+quartz=wollastonite+anorthite in the amphibolite-facies and granulite-facies terrains, respectively. The latter is the best-defined isograd among those so far drawn in various rock types of the Lutzow-Holm Complex, as it is based on a vapor-absent reaction and the effects of additional components such as Fe_2O_3 and Na_2O on the reaction are estimated to have been negligible in the studied rocks. Pressure of about 7kb is evaluated by the discontinuous reaction at T=810±20℃ in the granulite-facies terrain. The present study, together with the previously published ones, confirms that the regional metamorphic geotherm of the Lutzow-Holm Complex based on the progressive mineral zones was of the medium-pressure type and was distinct from those of the adjacent Rayner and Yamato-Belgica Complexes. The occurrence of grossular with or without quartz in the granulite-facies terrain suggests that the vapor phase was generally poor in both H_2O and CO_2 during the high-grade metamorphism. departmental bulletin paper